Two Sides of a Coin: Safe Space & Segregation in Race/Ethnic-Specific Law Student Organizations - Meera E. Deo (Washington University Journal of Law & Policy, 2013)
American racism and discrimination continue to plague our institutions of higher education. Predominantly white law school environments are especially notable for being inhospitable and unfriendly, especially for students of color. Many law students of color create and join race/ethnic-specific organizations in order to receive support on otherwise unwelcoming campuses. This Article analyzes data from a mixed-method empirical research study investigating student perceptions of race/ethnic-specific campus organizations. While many students view these groups as a safe space that provides a buffer from the rest of law school life, others worry that these organizations may increase segregation. Which perception is correct? When considered through a lens of racial privilege and utilizing a Critical Race Theory framework, we see that “exclusion” may have different meanings and outcomes based on the positionality of the groups involved. What some consider “self-segregation” may be necessary for creating safe space for otherwise marginalized students.
Keywords: Privilege Revealed; Critical Race Theory; privilege; student organizations; law school; perspectives on Diversity; POD; Safe Space Havens; Plessy v. Ferguson; Brown v. Board of Education; recognizing privilege